A concise guide to clinical reasoning. Issue 5 (30th April 2018) - Daly, Patrick
Abstract: What constitutes clinical reasoning is a disputed subject regarding the processes underlying accurate diagnosis, the importance of patient‐specific versus population‐based data, and the relation between virtue and expertise in clinical practice. In this paper, I present a model of clinical reasoning that identifies and integrates the processes of diagnosis, prognosis, and therapeutic decision making. The model is based on the generalized empirical method of Bernard Lonergan, which approaches inquiry with equal attention to the subject who investigates and the object under investigation. After identifying the structured operations of knowing and doing and relating these to a self‐correcting cycle of learning, I correlate levels of inquiry regarding what‐is‐going‐on and what‐to‐do to the practical and theoretical elements of clinical reasoning. I conclude that this model provides a methodical way to study questions regarding the operations of clinical reasoning as well as what constitute significant clinical data, clinical expertise, and virtuous health care practice.